A qualitative study of facilitators and barriers to healthy eating among older adults in China based on nutritional literacy and the capability opportunity motivation behaviour model - Qian Li; Qian Wang (Scientific Reports)
Abstract Nutritional literacy is a crucial determinant of healthy dietary behaviors, particularly for older adults who face increased risks of malnutrition and chronic diseases. This study integrates Nutbeam’s health literacy framework and the COM-B model (Capability, Opportunity, Motivation-Behavior) to explore factors influencing nutritional literacy and dietary behaviors among older adults in China. A qualitative study was conducted with 20 participants aged 60 years or older, recruited using purposive sampling from Jiangsu Province. Semi-structured interviews were conducted from October to November 2024. Data were analyzed thematically following Braun and Clarke’s framework, using NVivo software for data organization. Functional nutritional literacy relied on trusted sources such as healthcare providers and family, but participants faced challenges with food labels and online information. Interactive literacy was fostered through family discussions and community programs, though generational gaps and health limitations posed barriers. The COM-B model highlighted capabilities in dietary adjustments, limited access to affordable healthy foods, and strong motivation driven by health goals and family encouragement as determinants of dietary behavior. Improving functional, interactive, and critical nutritional literacy through tailored interventions is vital. Policies to enhance digital inclusion, lower healthy food costs, and strengthen community resources can support healthier dietary behaviors and contribute to successful aging.